Detecting the Herding Behaviour in the South African Stock Market and its Implications - Enow, Samuel Tabot (International Journal of Economics and Financial Issues, 2023)
Herd mentality is associated with financial market bubbles and crises and is not a new concept. Despite the dotcom bubble in the late 90’s and the recent real estate bubble, investors still have the tendency to see irrational decision as rational. Thus the aim of this study was to investigate the presence of herding in the Johannesburg stock exchange during the Covid-19 pandemic. Studies conducted in other markets have detected the presence of herding which sends strong signal of issues that may arise in financial markets. Using a sample period from 02 January 2020 to 31 December 2021 and a cross sectional absolute deviation as an analysis tool, the findings reveals a significant presence of herding in the Johannesburg stock exchange. The main implications to this finding is that momentum investing strategies is more suitable for the Johannesburg Stock exchange and exploring past price movements may provide valuable insights on expected future price movements